Sustainable wine preferences in China: scenario-specific insights for self-consumption and gift-giving - Hu, Ding; Ding, Ye; Zeng, Yinchu (Frontiers in Sustainable Food Systems, 2025)
China's wine market is increasingly driven by a demand for sustainability, influenced by diverse consumer behaviors and preferences. This study investigates sustainable wine preferences across self-consumption and gift-giving contexts in two western second-tier Chinese cities, using a choice experiment and Latent Class Model (LCM). Through a three-step analysis—evaluating the relative importance of attributes, marginal effects, and willingness to pay—we identify five distinct consumer segments based on two independent samples: “Price-Sensitive Consumers,” “Well-Known Area Followers,” and “China-Wine Enthusiasts” for self-consumption, and “Packaging Lovers” and “Organic Supporters” for gift-giving. Preference differences reveal distinct patterns relevant to sustainability. For instance, “China-Wine Enthusiasts” prefer local wines, supporting regional branding as a low-carbon option. “Organic Supporters” exhibit high WTP for organic labels, while “Packaging Lovers” favor delicate packaging, suggesting a need for more sustainable packaging alternatives. These findings highlight the importance of tailoring marketing strategies to consumer segments and consumption contexts within China's evolving wine market.